Germany : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Germany during 1990-95. In early 1995, both western and eastern Germany seemed well poised to continue on their respective growth paths. However, the economy was then confronted by a sharp nominal appreciation of the deutsche mark-translating into a 5 1\2 percent real effective appreciation between December 1994 and June 1995, most of it during February-which brought with it significant risks to exports and thereby to investment and to the recovery in general.